Construction of E-commerce Recommendation System based on Semantic Annotation of Ontology and User Preference - Hongsheng Xu; Ruiling Zhang; Chunjie Lin; Wenli Gan (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Ontology is an explicit formal specification of the shared conceptual model. Domain ontology can accurately describe the contents of the e-commerce site in the stage of built domain ontology. Web domain ontology can effectively improve the quality of the recommended use of the e-commerce personalized recommendation. The paper presents construction of e-commerce recommendation system based on semantic annotation of ontology and user preference.  In this paper domain ontology semantic annotation for the project is established, and this ontology takes advantage of semantic similarity measure to calculate the semantic similarity between the projects, and it can predict the score of unbranded items based on user ratings. The experimental results show that the algorithm recommended more effective than traditional algorithms, to improve the quality of the recommended. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4132